ANALISIS KINERJA GURU DENGAN MEMPERHATIKAN FAKTOR BUDAYA ORGANISASI, KOMPETENSI GURU DAN KEPEMIMPINAN KEPALA SEKOLAH MAN 5 BIREUEN - Munawwarah, Munawwarah; Fauzi, Fauzi (IndOmera, 2023)
The aim of the study was to analyze the relationship between organizational culture, teacher competency and principal leadership on teacher performance, either partially or simultaneously. The research was conducted using quantitative methods with multiple linear regression analysis. The research objects were 49 teachers at Madrasah Aliyah Negeri (MAN) 5 Bireuen Regency. The data collection technique uses a questionnaire. The results showed that: 1) There is a relationship between the variables of organizational culture, teacher competency and principal leadership on a moderate scale, 2) there is a partial influence of the three predictor variables namely organizational culture, teacher competency and principal leadership on teacher performance. 3) together with organizational culture, teacher competence and leadership